Autoignition of ternary blends for gasoline surrogate at wide temperature ranges and at elevated pressure: Shock tube measurements and detailed kinetic modeling. (1st October 2016) - Li, Hua; Yu, Liang; Lu, Xingcai; Ouyang, Linqi; Sun, Shuzhou; Huang, Zhen
Highlights: Three ternary gasoline surrogates with the same RON95 were constructed. Ignition delay of four toluene reference fuels was measured in shock tube. A detailed chemical kinetic model for the ternary gasoline surrogates was established. The ignition properties and reaction pathways of TRFs were analyzed. A comparison of ignition characteristics of toluene reference fuels with same RON was made. Abstract: Considering the diverse compositions of commercial gasoline, the ignition delay time of toluene reference fuels (TRF) composed of isooctane, n-heptane and toluene was studied in a shock tube under the conditions of medium to high temperature ranges, different pressures (10–20 bar), and various equivalence ratios (0.5, 1.0, 1.5 and 2) by reflected waves. To analyze the impacts of the component proportion on the gasoline surrogate combustion process, three different ternary blends, TRF2 (42.8% isooctane/13.7% n-heptane/43.5% toluene), TRF3 (65% isooctane/10% n-heptane/25% toluene) and TRF4 (87.2% isooctane/6.3% n-heptane/6.5% toluene), with the same Research Octane Number of 95 (RON = 95) were constructed; TRF1 was the same as Surrogate A in Gauthier et al. (2004). The experimental results showed that there was an obvious negative correlation between the ignition delay time of the toluene reference fuels and the pressure, temperature and equivalence ratio; notably, the measured data showed a minimal discrepancy of TRF2, TRF3, and TRF4 at pressures of 10 and 20 bar in a stoichiometric ratio. Based on Curran's (2002) detailed kinetic model for PRF (primary reference fuel) and Yuan's (2015) toluene pyrolysis and oxidation model, which updated and integrated the thermodynamic parameter and reaction rate for some key reactions, a detailed chemical mechanism consisting of 1251 species and 5705 reactions was established to illustrate the surrogate combustion properties. The model captured the autoignition behavior of all four ternary gasoline surrogates well in the shock tube experiments, especially at high pressure and under rich fuel conditions. Furthermore, the sensitivities and a reaction pathway analysis were also calculated for different blending ratios using CHEMKIN-PRO software, which exhibited and analyzed partial ignition features with respect to the chemical reactions based on the model proposed in this work.